Strategi Pengembangan Kawasan Wisata Hutan Mangrove Lantebung Kota Makassar - Valentino Sarapang Batara; Agus Salim; Jufriadi Jufriadi (Journal of Urban Planning Studies, 2020)
Valentino Sarapang Batara, 2020. Development Strategy for the Tourism Area of the Lantebung Mangrove Forest in Makassar City. Supervised by Agus Salim and Jufriadi. This study aims to determine how the carrying capacity of the area towards tourism activities in the Lantebung mangrove forest tourism object and provide strategies in developing the Lantebung mangrove forest tourism area. This study uses a qualitative approach method and a quantitative approach to the data collection process through observation, structured interviews and documentation. The sampling technique used was purposive sampling. The analysis used is the calculation of the carrying capacity of the mangrove tourism area and the SWOT analysis. The results of this study indicate that the Lantebung mangrove forest tourism area is suitable for tourism activities with a suitability value of 61.73%. The carrying capacity of the tourist area only allows visitors of 250 peoples/day. The strategy obtained to develop the Lantebung mangrove forest tourism area is to minimize weaknesses by taking advantage of opportunities. Keywords : Strategy, Area Supporting Capacity, Tourism, Mangrove, Lantebung.